Effects of school-based intervention by emergency medical technicians on students and their parents: a community-based prospective study of the Akashi project - Tomari, Shinya (BMJ Open, 2017)
OBJECTIVE: Stroke lessons for youth provided by emergency medical technicians (EMTs) may be an effective strategy to facilitate early intervention for patients with stroke. The aim of this study was to examine how effective EMT-led lessons on stroke awareness for schoolchildren were at disseminating stroke information. SETTING, PARTICIPANTS AND OUTCOME MEASURES: The study was performed in the city of Akashi, Hyogo, Japan (Akashi project). Children (aged 9–10 years old) at 11 public elementary schools and their parents were enrolled in this study. EMTs from the firefighting headquarters provided lessons on stroke to the children using our educational materials between September 2014 and October 2015. Each child was given our educational materials to take home and discuss stroke with their parents. The children and their parents answered questionnaires on stroke knowledge before, immediately and at 3 months after the lesson. RESULTS: A total of 763 children and 489 parents were enrolled (ie, 64% of children). The scores of either stroke symptoms or risk factors were significantly higher immediately and at 3 months after the lesson, compared with before the lesson, both in children and the parents (p<0.01). Compared with the baseline in both groups (58% in children, 83% in parents), the meaning of the FAST mnemonic at 3 months (88%, 94%), as well as at immediately after the lesson (90%, 89%), was significantly higher (p<0.001). CONCLUSION: Stroke education by EMTs was effective in increasing stroke awareness in elementary school children, as well as their parents.